2008
DOI: 10.1016/j.neuron.2008.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling through Synchrony in Neuronal Circuits with Propagation Delays

Abstract: The level of synchronization in distributed systems is often controlled by the strength of the interactions between individual elements. In brain circuits the connection strengths between neurons are modified under the influence of spike-timing-dependent plasticity (STDP) rules. Here we show that when recurrent networks with conduction delays exhibit population bursts, STDP rules exert a strong decoupling force that desynchronizes activity. Conversely, when activity in the network is random, the same rules can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
180
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(197 citation statements)
references
References 39 publications
16
180
1
Order By: Relevance
“…While some memories integrate content from single sensory modalities, requiring consolidation in only single cortical regions (such as motor cortex, Khazipov et al, 2004), many memories integrate multimodal sensory and cognitive information (Gibson and Maunsell, 1997), and require 'global' integration of distributed networks across the cortex. In this work, we have identified a novel mechanism by which this process could occur: the stereotyped activity patterns reported here may enable STDP to establish large-scale neuronal assemblies at scales where axonal conduction delays are long relative to the oscillation cycle (Fries, 2005;Lubenov and Siapas, 2008), and repeat many times throughout sleep with millisecond accuracy. While the schema illustrated in Figure 2 is a highly simplified view of the microscale interactions between long-range excitatory projections and local networks during spindle oscillations, computational and theoretical studies have previously obtained a detailed understanding of STDP dynamics with neurons receiving sequenced Sejnowski, 2001, 2003), bursting (Song et al, 2000), and oscillating inputs (Muller et al, 2011;Luz and Shamir, 2016).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…While some memories integrate content from single sensory modalities, requiring consolidation in only single cortical regions (such as motor cortex, Khazipov et al, 2004), many memories integrate multimodal sensory and cognitive information (Gibson and Maunsell, 1997), and require 'global' integration of distributed networks across the cortex. In this work, we have identified a novel mechanism by which this process could occur: the stereotyped activity patterns reported here may enable STDP to establish large-scale neuronal assemblies at scales where axonal conduction delays are long relative to the oscillation cycle (Fries, 2005;Lubenov and Siapas, 2008), and repeat many times throughout sleep with millisecond accuracy. While the schema illustrated in Figure 2 is a highly simplified view of the microscale interactions between long-range excitatory projections and local networks during spindle oscillations, computational and theoretical studies have previously obtained a detailed understanding of STDP dynamics with neurons receiving sequenced Sejnowski, 2001, 2003), bursting (Song et al, 2000), and oscillating inputs (Muller et al, 2011;Luz and Shamir, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…It is well established that sleep oscillations actively contribute to this process: during stage 2 sleep spindles, the thalamus generates a rhythmic activity pattern that becomes widespread through large-scale thalamocortical loops , and spindles are critical to sleep-dependent memory consolidation (Gais et al, 2002;Mednick et al, 2013). Long-range connections in cortex result primarily from excitatory pyramidal cells (Sholl, 1956;Schüz et al, 2002), but precisely how sleep oscillations aid strengthening of these excitatory connections between distributed cortical networks through spike-time dependent plasticity (STDP) remains unclear, particularly in the presence of long axonal conduction delays (Lubenov and Siapas, 2008). Here, we identify a global activity pattern repeatedly observed during sleep spindle oscillations in human neocortex that could serve this role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular and electrophysiological markers of synaptic potentiation increase after waking in rat cortex and hippocampus, while markers of synaptic depression do so after sleep. 5,6 Moreover, in rats and humans, procedures presumably leading to synaptic potentiation or depression result in SWA increases and decreases, respectively. [7][8][9][10][11][12] More specifically, a study in humans using highdensity EEG found that performing a visuomotor learning task produced a local increase in SWA during subsequent sleep.…”
Section: Sleep Is Present and Homeostatically Regu-lated In All Animamentioning
confidence: 99%
“…A desirable temporal output for granular synthesis in music would be a controllable signal, which lies at the border between randomness and synchrony. Two-dimensional reduced spiking neuronal models (reduced from the four-dimensional HodgkinHuxley model [10]) have been shown recently to self-organise at this boundary [11]. Recent artistic projects, The Fragmented Orchestra [7] and the Neurogranular Sampler [5] [7] focused on the two-dimensional Izhikevich spiking network model [8] and trigger sound samples upon neuronal firing.…”
Section: Figmentioning
confidence: 99%